Teaching Microbiome Analysis: From Design to Computation Through Inquiry - Rosen, Gail L.; Hammrich, Penny (Frontiers in Microbiology, 2020)
In this article, we present our three-class course sequence to educate students about metagenomics through experiential learning by taking them from inquiry to analysis of the microbiome: Molecular Ecology Lab, Bioinformatics, and Computational Metagenomics. Students developed hypotheses, designed lab experiments, sequenced the DNA from microbiomes, learned basic python/R scripting, became proficient in at least one metagenomics analysis software, and were able to analyze data generated from the microbiome experiments. Over 150 students (graduate and undergraduate) were impacted by the development of the series of courses. Generally, more positive attitudes towards bioinformatics were received through surveys and private correspondence. Through a summative assessment, general trends show that students became more proficient in comparative genomic techniques and had positive attitudes towards their abilities to bridge biology and bioinformatics. It is expected that students trained will enter the workforce with skills needed to innovate in the biotechnology, health, and environmental industries. Students are trained to maximize impact and tackle real world problems in biology and medicine with their learned knowledge of data science and machine learning. The course materials for the new metagenomics course are available on Github: https://github.com/EESI/Comp_Metagenomics_resources